Analysing the direct and indirect effects of entrepreneurial competencies on international market diversification and profitability: a study of small exporting firms in Ghana. (22nd August 2019) - Oppong, Prince Kwarteng; Dornberger, Utz; Nabi, Md. Noor Un
The study analyses the direct and indirect effects of entrepreneurial competencies (ECs) on the international performance of small exporting firms. Considering the high importance of ECs, it particularly looks at their direct and indirect impacts on international market diversification (IMD) and profitability. We contribute to the growing research in special areas of internationalisation of SMEs and underscored particular competencies for internationalisation, their interactions and relationships as well as implications for small exporting firms in Ghana and their international performance. Primary data was collected through a survey of 134 small exporting firms from different sectors in Ghana and analysed with structural equation modelling, which was made of nine constructs. The study showed that five identified ECs have direct positive effects on IMD, which also leads to a superior rate of profitability. It furthermore highlighted the mediation effect of IMD which caused indirect effects of ECs on profitability.